2015
DOI: 10.4162/nrp.2015.9.6.592
|View full text |Cite
|
Sign up to set email alerts
|

The micosporine-like amino acids-rich aqueous methanol extract of laver (Porphyra yezoensis) inhibits adipogenesis and induces apoptosis in 3T3-L1 adipocytes

Abstract: BACKGROUND/OBJECTIVESIncreased mass of adipose tissue in obese persons is caused by excessive adipogenesis, which is elaborately controlled by an array of transcription factors. Inhibition of adipogenesis by diverse plant-derived substances has been explored. The aim of the current study was to examine the effects of the aqueous methanol extract of laver (Porphyra yezoensis) on adipogenesis and apoptosis in 3T3-L1 adipocytes and to investigate the mechanism underlying the effect of the laver extract.MATERIALS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…However, it is interesting to note that EHPP can significantly reduce body weight and fat content by intragastric administration, which may inhibit the risk of obesity and need to be explored in the future research. Similarly, previous studies have shown that the treatment with porphyra extract, lipid accumulation is inhibited in the cell (Kim et al, 2015).…”
Section: Discussionsupporting
confidence: 73%
“…However, it is interesting to note that EHPP can significantly reduce body weight and fat content by intragastric administration, which may inhibit the risk of obesity and need to be explored in the future research. Similarly, previous studies have shown that the treatment with porphyra extract, lipid accumulation is inhibited in the cell (Kim et al, 2015).…”
Section: Discussionsupporting
confidence: 73%
“…The 3T3-L1 mouse preadipocytes have been widely used for screening the effective agents to regulate the adipogenesis. The adipogenesis was determined by Oil Red O staining to show the amount of lipid droplets by specifically staining neutral triglycerides with high levels of adiopocyte-related genes expression in 3T3-L1 cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Kim et al [ 22 ] indicated that Pyropia yezoensi ( P. yezoensis ) methanol extract, one types of laver contain high MAAs content (120 mg/g dried extract) reduces the contents of accumulation lipid determined by Oil Red O staining in a dose-dependent manner [ 22 ]. However, they demonstrated that treatment with high concentration (5 mg/mL) of the P. yezoensis methanol extract inhibited adipogenesis with decrease of preadipocytes proliferation via oxidative stress and proapoptotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Among Porphyra yezoensis is an edible red alga called Gim in Korean ( nori in Japan) cultivated and consumed mainly in Korea, Japan, and China . P. yezoensis is rich in proteins and polysaccharides, and several pharmacological properties have already been elucidated for it, such as hypolipidemic and liver protective, antioxidant and anti‐inflammatory, and pro‐apoptotic and anti‐adipogenic effects. Furthermore, polysaccharide fractions of P. yezoensis yielded from hot water have been revealed to augment macrophage activity and interleukin (IL)‐1 secretion, whereas acid extract has been identified to activate macrophages which are isolated from the peritoneal cavity of mice under proteose peptone activation .…”
Section: Introductionmentioning
confidence: 99%